FAKTOR-FAKTOR PENYEBAB HIPEREMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER 1 - Etika Dewi Cahyaningrum; Riska Oktafiyani (Universitas Harapan Bangsa Purwokerto, 2009)
Hyperemesis gravidarum light is a common complaint (physiological) does in the youngpregnancy. Hyperemesis gravidarum were mild (grade I) experienced continuously causepregnant women or people with weak, loss of appetite and lack of intake of healthy foods, itcertainly can affect fetal development and maternal worsen and lead to hyperemesisberat.Tempat research in hospitals Prof.Dr Margono Soekarjo the year 2009 as many as 52respondents.The purpose of this research know the description of events hyperemesis gravidarum in pregnantwomen in hospitals Prof. Dr. Margono Soekarjo Purwokerto, 2009.This study design using quantitative descriptive retrospective approach. Samples are allpregnant women with hyperemesis gravidarum in 2009 as many as 52 cases in hospitals Prof.Dr. Margono Soekarjo Purwokerto. Sampling using total sampling technique.The results showed the incidence of hyperemesis gravidarum in pregnant women the firsttrimester is the most widely primigravida and multigravida many as 23 respondents (47.9%),most of these occurrences aged 20-35 years were 19 respondents (35.4%), and based on ahistory of multiple pregnancy as much as 2 respondents (4.2%).Keywords: Hyperemesis Gravidarum, age, gravida, history of multiple pregnancy